Du presque-rien au presque-tout : le dévoilement de l’invisible dans Trifles (1916) de Susan Glaspell - Emeline JOUVE (E-REA)
Produced in 1916 by the Provincetown Players, the play Trifles by Susan Glaspell, defined by scholars as “the mother of the Modern American theatre,” stages the unveiling of the invisible. A crime has been committed in the Wrights’ farm and the representatives of the law, accompanied by the wives, have come to find evidence to convict Mrs. Wright of the murder of her husband. In this detective play, the chiaroscuro effect appears as a principle which structures this work in which the playwright literalizes the metaphor of social invisibility to denounce patriarchal oppression and encourage the audience to reflect upon the mechanisms underpinning the norms on which the society of the beginning of the 20th century was based.